THE IMPORTANCE OF COMMUNICATIVE GAMES IN ENGLISH LESSONS - Soatov Ibrohimbek; Raimov Olimjon (TADQIQOTLAR, 2025)
Annotation: This article explores the significant role communicative games play in enhancing the effectiveness of English language lessons. It examines how such games foster student engagement, promote active language use, and create a dynamic classroom atmosphere conducive to learning. The paper highlights the psychological and linguistic benefits of incorporating games, such as reducing anxiety, increasing motivation, and improving speaking and listening skills. It also presents practical examples of communicative games suitable for various language proficiency levels, offering valuable insights for teachers aiming to develop interactive and learner- centered lessons. The study concludes that communicative games are not just supplementary tools but essential strategies for developing students’ communicative competence and confidence in using English.